Arlo needs glasses - Saltzberg, Barney (Workman Pub., 2012)
After visiting the eye doctor and getting fitted with glasses, Arlo the dog is able to catch the ball thrown by his owner. Includes eye chart, fold-out vision-testing machine, and four pairs of try-on glasses.